2007
DOI: 10.1063/1.2793744
|View full text |Cite
|
Sign up to set email alerts
|

Spin solitons in magnetized pair plasmas

Abstract: A set of fluid equations, taking into account the spin properties of the electrons and positrons in a magnetoplasma, are derived. The magnetohydrodynamic limit of the pair plasma is investigated. It is shown that the microscopic spin properties of the electrons and positrons can lead to interesting macroscopic and collective effects in strongly magnetized plasmas. In particular, it is found that new Alfvénic solitary structures, governed by a modified Korteweg-de Vries equation, are allowed in such plasmas. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
85
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 46 publications
0
85
0
Order By: Relevance
“…[6][7][8][9][10] In dense plasmas the degenerate electrons follow Fermi-Dirac statistics, and there are quantum tunneling [11][12][13][14][15][16] and spin [17][18][19][20] forces due to the spread in the electron probability wave function. The quantum statistical electron pressure and quantum Bohm forces produce wave dispersions at nanoscales.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] In dense plasmas the degenerate electrons follow Fermi-Dirac statistics, and there are quantum tunneling [11][12][13][14][15][16] and spin [17][18][19][20] forces due to the spread in the electron probability wave function. The quantum statistical electron pressure and quantum Bohm forces produce wave dispersions at nanoscales.…”
Section: Introductionmentioning
confidence: 99%
“…the interior of white dwarf stars, magnetars, giant planetary interiors), and in the next generation intense laser-solid density plasma experiments [4,5,6,7,8]. In dense plasmas the degenerate electrons follow Fermi-Dirac statistics, with quantum tunneling [9,10,11,12,13,14,15] and spin [16,17,18,19,20] forces due to the spread in the electron probability wave-function. The quantum statistical electron pressure and quantum forces produce wave dispersion at nanoscales.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations indicate that the spin properties of the electrons and positrons can lead to interesting collective effects in quantum magnetoplasmas [19]. More recently, it has been shown that the electron spin 1/2 effect significantly modifies the dynamics [21] and modulational instability domain [22] of magnetosonic solitary waves and the collective effects in strongly magnetized plasmas [23].…”
mentioning
confidence: 99%